2023
DOI: 10.1021/acsanm.2c04680
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Selenium Vacancies on CoSe2 Nanoarrays for Alkaline Hydrogen Evolution

Abstract: The development of highly efficient nonnoble metals toward hydrogen evolution reaction (HER) electrocatalysts is significant for producing hydrogen via water electrolysis. Selenides are becoming increasingly attractive owing to their excellent HER activity. Herein, CoSe2 nanorods were successfully manufactured on a carbon cloth (CC) and selenium vacancies were obtained using a plasma cleaner (CoSe2-VSe/CC) to enhance their intrinsic catalytic activity. The synthetic catalyst exhibited a lower overpotential of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Pan et al demonstrated that the HER of CoSe 2 nanorods could be promoted by the introduction of Se-vacancy. [68] The CoSe 2 nanorods with an abundance of vacancies were synthesized through subjecting CoSe 2 supported on carbon cloth (CC) to plasma treatment for varying treatment time (CoSe 2 -V se /CC-x, x: plasma treatment time). Figure 9a displays SEM images of CoSe 2 nanorods covering the surface of CC.…”
Section: Vacancy and Defect Engineeringmentioning
confidence: 99%
“…Pan et al demonstrated that the HER of CoSe 2 nanorods could be promoted by the introduction of Se-vacancy. [68] The CoSe 2 nanorods with an abundance of vacancies were synthesized through subjecting CoSe 2 supported on carbon cloth (CC) to plasma treatment for varying treatment time (CoSe 2 -V se /CC-x, x: plasma treatment time). Figure 9a displays SEM images of CoSe 2 nanorods covering the surface of CC.…”
Section: Vacancy and Defect Engineeringmentioning
confidence: 99%
“…Transition metal sulfides, 18–21 selenides, 22–24 phosphates, 25–27 carbides 28–30 and other compounds with high activity and conductivity have drawn a lot of attention in the field of hydrogen evolution catalysts. CoP is a promising catalyst for hydrogen evolution among transition metal compounds due to its high HER activity, excellent stability and excellent conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the high price and scarcity of these noble metals seriously impede their application. 6 Thus, it is crucial to exploit alternative, inexpensive, and highly active noble-metal-free electrocatalysts, such as transition metal (TM)-based materials. However, the performance of the TM-based electrocatalysts usually suffers from their sluggish kinetics with larger overpotential.…”
Section: Introductionmentioning
confidence: 99%